2014
DOI: 10.1161/circheartfailure.113.000527
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Intensified, N-Terminal-Pro-B-Type Natriuretic Peptide–Guided Versus Symptom-Guided Treatment in Elderly Patients With Heart Failure

Abstract: Background— Therapy guided by N-terminal-pro-B-type natriuretic peptide (NT-proBNP) levels may improve outcomes in patients with chronic heart failure (HF), especially in younger patients with reduced left ventricular ejection fraction. It remains unclear whether treatment effects persist after discontinuation of the NT-proBNP–guided treatment strategy. Methods and Results— Trial of Intensified versus standard Medical therapy in Elderly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Long-term follow-up is not available for most RCTs. In the TIME-CHF, 86 BNP-guided therapy ceased at 18 months; over a 5-year follow-up period, the study found a non-significant trend for continued improved survival in younger HFrEF patients with treatment guided by BNP (HR 0.62, 95% CI 0.37 to 1.03). Very few patients were followed up for the full 5 years in TIME-CHF.…”
Section: Model-based Cost-effectiveness Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…Long-term follow-up is not available for most RCTs. In the TIME-CHF, 86 BNP-guided therapy ceased at 18 months; over a 5-year follow-up period, the study found a non-significant trend for continued improved survival in younger HFrEF patients with treatment guided by BNP (HR 0.62, 95% CI 0.37 to 1.03). Very few patients were followed up for the full 5 years in TIME-CHF.…”
Section: Model-based Cost-effectiveness Analysismentioning
confidence: 94%
“…Statistically, there was relatively little variation in the mortality outcomes of RCTs; however, there were important differences in the BNP-guided monitoring protocols used. TIME-CHF, 86 which has provided the best evidence to date of a sustained effect in younger patients with HFrEF, scheduled visits at 1, 3, 6, 12 and 18 months with the aim of rapidly up-titrating therapy within 6 months. However, other protocols may be more cost-effective.…”
Section: Lessons For the Future: Implications For Clinicians And Polimentioning
confidence: 99%
“…Several potential reasons may explain our observations. BNP‐guided therapy does not always improve clinical outcomes as previously reported 9, 10, 11. The reason for this lack of significant improvement may be that BNP levels only change upon ventricular wall stretching.…”
Section: Discussionmentioning
confidence: 71%
“…Elevated MMP‐9 levels may help identify patients at risk before an increase occurs in ventricular pressure overload, which reflects ongoing ventricular remodeling. The value of BNP levels for guiding therapy in addition to clinical symptom‐based treatment seems to be limited,9, 10, 11, 21 despite the undisputed diagnostic and prognostic importance of these values 6, 7, 8. The benefits of predicting HF events may be offset by non‐HF events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation